Electrically conductive graphene-coated polyurethane foam and its epoxy composites - Xinzhao, Xu; Guoming, Lin; Dongyan, Liu; Guoxin, Sui; Rui, Yang (Composites communications, 2018)
A facile method is presented to manufacture electrically conductive graphene-coated polyurethane foam (GPF) by dip-coating polyurethane (PU) foams in a graphene (GN) aqueous suspension containing cellulose nanowhisker (CNW) as dispersion assistant. The electrical conductivity of the GPF/epoxy composites reaches 2.46S/m at a relatively low GN content (0.9wt%), and the electrical percolation threshold is around 0.3wt%. The structure observations reveal that the high electrical conductivity results from the 3D networks formed by GN nanosheets coated on the inner surface of PU foams. Moreover, CNW is a key factor to facilitate the formation of GN networks on the PU skeleton. The highest electrical conductivity is obtained at the CNW / GN weight ratio of 1:20. •Highly conductive GPFs and GPF/epoxy composites were fabricated via template-based dip-casting and vacuum assisted infiltration.•Integral 3D GN networks were formed in the composites.•CNW facilitated the formation of GN networks on the PU skeleton.